La sexualidad pensada en términos masculinos: el caso de las mujeres Wayuu en la Guajira colombiana - Martínez Osorio, Margarita (CUADERNOS KÓRE, 2012)
The aim of this paper is to analyze the case of violence against Wayuu’s women of the Guajira, Colombia, based on the feminist theory of Catherine Mackinnon, as well as the justice’s outline of Nancy Fraser. Taking this into account, the analysis is developed from two sides: on one hand I examine the structural grounds that leaded slaughter on, and that propitiated the use of one sort of siege’s mechanism and excluded the others. On the other hand I focus on proposing a set of necessary conditions which guarantee an appropriate process of retrieval to the violated Wayuu community. The concept of sexuality is essential as a conceptual articulation of the whole text, because it guides the interpretation of the facts that occurred in the Guajira.
Keywords: sexuality; public awareness; justice; exemplary punishment